Development and Evaluation of a Multifunctional Illuminated Dental Mirror to Improve Patient Comfort During Restorative Procedures - Pujianti, Anita; Ningtyas, Endah Aryati Eko; Suwondo,, Ari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: The dental mouth mirror is a primary diagnostic tool used by oral health professionals to examine the condition of the oral cavity. However, conventional mouth mirrors often face obstacles. Around 53% of dental health professionals report difficulties in providing care due to frequent fogging and dirt accumulation on the mirror surface. Field examinations also often encounter problems due to limited lighting. Patient comfort must also be considered during procedures, as it affects the healing process. Therefore, an innovative dental examination instrument with integrated lighting was developed to enhance patient comfort during treatment.Method: This study used a Research and Development (R&D) approach along with a true experimental design, specifically a posttest-only with control group design. The sampling technique used was purposive sampling, involving 60 dental filling patients who met the inclusion criteria. Product testing data were analyzed using the descriptive statistics, and the Mann-Whitney test.Result: Expert validation of the dental examination instrument with integrated lighting yielded an average feasibility score of 83.3% (classified as highly feasible) with a p-value of 0.00. The effectiveness test of the tool showed a significant improvement in patient comfort (p = 0.000).Conclusion: The dental examination instrument with integrated lighting has been validated and proven effective in improving patient comfort during dental filling procedures performed by oral health professionals.